The San Francisco Calamity by Earthquake and Fire - Morris, Charles, 1833-1922 (Salt Lake City, UT : Project Gutenberg, 2006)
"The San Francisco Calamity by Earthquake and Fire" by Charles Morris is a historical account written in the late 19th to early 20th century. The narrative details the catastrophic events of the 1906 San Francisco earthquake and fire, which devastated the city and resulted in the loss of countless lives and properties, as well as a monumental humanitarian crisis. The book is framed through eyewitness accounts, chronicling the chaos and horror experienced by the nearly 300,000 individuals left homeless and the city's struggle for survival amidst the overwhelming discord wrought by nature. The opening of the book sets the stage for the subsequent calamity, describing the flourishing city of San Francisco prior to the disaster. It provides a foreboding introduction to the geological vulnerabilities of the area, referencing the city's rapid growth and unique structures before the feared earthquake unleashes its fury. The chapter highlights the moment of awakening on April 18, 1906, detailing the chaos as buildings crumbled, city streets transformed into chaotic voids, and the panicked exodus of residents attempting to flee the growing disaster. The narrative emphasizes the ensuing destruction by fire that followed the quake, weaving personal accounts of horror, bravery, and desperation among the populace as they grappled with the aftermath of such an unimaginable event. (This is an automatically generated summary.)
Release date is 2006-05-03
Produced by Donald Lainson; David Widger
Keywords: San Francisco Earthquake and Fire, Calif., 1906; Earthquakes -- California -- San Francisco -- History -- 20th century; Fires -- California -- San Francisco -- History -- 20th century; San Francisco (Calif.) -- History -- 20th century; San Francisco (Calif.) -- Biography